Activation of pausing F(1) motor by external force - Hirono-Hara, Yoko (National Academy of Sciences, 2005)
A rotary motor F(1), a catalytic part of ATP synthase, makes a 120° step rotation driven by hydrolysis of one ATP, which consists of 80° and 40° substeps initiated by ATP binding and probably by ADP and/or P(i) dissociation, respectively. During active rotations, F(1) spontaneously fails in ADP release and pauses after a 80° substep, which is called the ADP-inhibited form. In the present work, we found that, when pushed >+40° with magnetic tweezers, the pausing F(1) resumes its active rotation after releasing inhibitory ADP. The rate constant of the mechanical activation exponentially increased with the pushed angle, implying that F(1) weakens the affinity of its catalytic site for ADP as the angle goes forward. This finding explains not only its unidirectional nature of rotation, but also its physiological function in ATP synthesis; it would readily bind ADP from solution when rotated backward by an F(o) motor in the ATP synthase. Furthermore, the mechanical work for the forced rotation was efficiently converted into work for expelling ADP from the catalytic site, supporting the tight coupling between the rotation and catalytic event.